Effect of biofertilizers and organic supplements on the growth of black pepper rooted cuttings (Piper nigrum L.) - T Sathyan, T T Preethy, M Murugan, T S Aswathy, M K Dhanya, J Johny, (Journal of Spices and Aromatic Crops, 2018)
An experiment was conducted at the Cardamom Research Station, Kerala Agricultural University, Pampadumpara (Kerala) with an objective to study the effect of different biofertilizers (Phosphorus solubilizing bacteria, Azospirillum and Plant Growth Promoting Rhizobacteria Mix I) and organic supplements (fish extract and humic acid) on the growth of black pepper rooted cuttings. The results of the experiment indicated that application of Phosphorus solubilizing bacteria (5 g) along with Azospirillum (5 g), humic acid (0.2%) and fish extract (0.5%) was the best combination for the production of black pepper rooted cuttings with improved vegetative characters (plant height, number of leaves, number of roots, length of roots and leaf area) compared to theirindividual inoculation.This innovative information can be effectively utilized and advocated for the commercial production of black pepper rooted cuttings with lusty growth.